2018
DOI: 10.1111/ene.13847
|View full text |Cite
|
Sign up to set email alerts
|

Burden of non‐motor symptoms in Parkinson's disease patients predicts improvement in quality of life during treatment with levodopa‐carbidopa intestinal gel

Abstract: Background and purpose GLORIA , a registry conducted with 375 advanced Parkinson's disease patients treated with levodopa‐carbidopa intestinal gel ( LCIG ) for 24 months in routine clinical care, demonstrated significant reductions from baseline in ‘off’ time and ‘on’ time with dyskinesia and improvements in the Non‐Motor Symptom Scale ( NMSS ) total and individual domain scores, and in Parkinson's Disease Questionnaire 8 item ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 35 publications
6
20
0
Order By: Relevance
“…Assessment of NMSs in PD are now key to value‐based health care and recommended by patient‐led organizations and the International Parkinson and Movement Disorder Society (IPMDS) . The availability of the NMSS has also allowed NMSs to be assessed in many clinical trials . The impact of NMS burden on quality of life across all stages of PD is now well established, and the NMSS has been used in PD subtyping studies …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of NMSs in PD are now key to value‐based health care and recommended by patient‐led organizations and the International Parkinson and Movement Disorder Society (IPMDS) . The availability of the NMSS has also allowed NMSs to be assessed in many clinical trials . The impact of NMS burden on quality of life across all stages of PD is now well established, and the NMSS has been used in PD subtyping studies …”
mentioning
confidence: 99%
“…3 The availability of the NMSS has also allowed NMSs to be assessed in many clinical trials. [4][5][6][7][8][9][10][11][12] The impact of NMS burden on quality of life across all stages of PD is now well established, and the NMSS has been used in PD subtyping studies. 13,14 The NMSS was developed approximately 15 years ago.…”
mentioning
confidence: 99%
“…Other studies reported that some NMS are more frequent in patients with motor complications [2,7], as in our stduy. All of these data suggest a link between motor and NMS [16]. Fatigue, difficulty concentrating, sadness, pain and other sensory symptoms are some examples of NMS frequently related to OFF state [14].…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy of up to 16-hours continuous administration of LCIG in reducing motor fluctuations has been established in multiple prospective studies [6][7][8][9][10][11][12][13][14][15][16][17][18], and reviewed extensively [2,[19][20][21]. Although the pathogenesis of NMS remains partially unclear, 16-hour (16-h) continuous administration of LCIG has been associated with improvements in NMS, sleep quality, and quality-of-life measures (Table 1) [6,7,11,13,17,22,23].…”
Section: Overviewmentioning
confidence: 99%
“…Data from the GLORIA registry demonstrated improvements in patient quality of life and reductions in NMS, including sleep and fatigue [ 6 , 7 ]. In addition, baseline NMS burden was associated with improvements in NMS and quality of life [ 22 ]. Similarly, in the GREENFIELD observational cohort, significant improvements were observed in quality of life, NMS, and sleep [ 13 ].…”
Section: Levodopa-carbidopa Intestinal Gelmentioning
confidence: 99%